EFFECT OF AFRICAN LEAF (VERNONIA AMYGDALINA) TO IL-6 AND IL-10 LEVEL ON STAPHYLOCOCCUC AUREUS INFECTION - Setiawan, Lidwina Tri Kristanti; Nugraha, Jusak; Lestari, Pudji; Sinansari, Restry; Soegianto, Lisa; Tamayanti, Wahyu Dewi; Handayani, Luh Putu Trys Monika; Beatrix, Stephanie (Indonesian Journal of Tropical and Infectious Disease, 2019)
Currently, infectious disease is increase in world wide. The African leaf (Vernonia amygdalina) – VA is used to antimicrobial treatment. It may protect the host against microbial attack in several ways. This plant has attracted the interest of researchers in recent decades because of the constituents have important roles in modulating immune system in bacteria infection. The aim of study is to analyze the prophylactic activity of VA's ethanol extract in modulating the levels of IL-6 and IL-10 as well as the number of bacteria in male Wistar rats that were (Staphylococcus aureus) – SA – infected. There were as many as 30 rats were divided into 5 treatment groups: negative control (NC) was treated by CMC Na 2% (w/v); positive control (PC) was treated by 9mg/200g body weight (BW) of cephadroxil; T1; T2; and T3 were respectively treated with ethanol extract of VA of doses 20mg/200g BW; 40mg/200g BW and 80mg/200g BW. After the oral treatment was administered, all the rats were infected with 0.25mL (3x108cfu) SA via intra peritoneal route. Their blood was drawn in order to identify the IL-6 and IL-10 levels by ELISA. Furthermore, their peritoneal fluid was also taken to count the number of survived bacteria by pour plate method. The results are showed median of IL-6 and IL-10 levels as well as bacterial number respectively in NC 370.530pg/mL; 67.044pg/mL; 7.4x103cfu/mL; in PC 234.556pg/mL; 42.839pg/mL; 6.8x103cfu/mL,; in  T1 164.019pg/mL; 17.240pg/mL; 1.1x104cfu/mL; in T2 49.291pg/mL; 2.961 pg/mL; 6.3x103cfu/mL and in T3 43.342pg/mL; 13.235pg/mL; 7.1x103cfu/mL. These results are implied that VA's ethanol extract is effective as a prophylactic agent to suppress the bacterial invasion at dose of 40mg/200g BW in Wistar rat particularly shown by the decrease level of IL-6 and the number of bacteria.